Зарубіжний досвід роботи з науковою молоддю на прикладі молодіжних академій - Вашуленко, О.С. (Наука та наукознавство, 2018)
Зарубіжний досвід роботи з науковою молоддю проаналізовано на прикладі діяльності молодіжних академій в різних країнах світу. Надано інформацію про історію створення Молодої академії в Німеччині, молодіжних академій в деяких інших країнах, Глобальної молодіжної академії, їх завдання, умови членства, а також заходи щодо заохочення талановитої молоді до наукової діяльності. Згідно з результатами дослідження, молодіжні академії функціонують у більш ніж 40 країнах світу. Досвід України у створенні молодіжних структур у науці показано на прикладі діяльності рад молодих учених. На підставі проведеного аналізу зроблено висновок щодо актуальності створення в Україні організації, подібної до молодіжної академії. В работе проанализирован зарубежный опыт работы с научной молодежью на примере молодежных академий в разных странах мира. Предоставлена информация об истории создания Молодой академии в Германии, молодежных академий в других странах, Глобальной молодежной академии, их задачи, условия членства, а также меры по привлечению талантливой молодежи к научной деятельности. Согласно результатам исследования, молодежные академии функционируют в более чем 40 странах мира. Опыт Украины в создании молодежных структур в науке показан на примере cоветов молодых ученых. На основании проведенного анализа сделан вывод об актуальности создания в Украине организации, подобной молодежной академии. Because engagement of the young generation in R&D is an issue of critical importance for Ukraine, the article contains an extensive review of foreign practices in working with scientific youth. It shows that the so called young academies which mission is to draw attention to the problems faced by young researchers represent a conventional form of work with scientific youth. According to official data, by 2017 young academies helping to enhance the R&D activity of young scientists had been created in 30 countries. The first young academy was created in Germany in 2000; similar academies were established thereafter in the Netherlands (2005), Sudan and Austria (2007). The article provides information about the history of the young academy in Germany and some other countries, the history of Global Young Academy (GYA) created in 2000, its objectives and membership conditions. A central purpose of GYA is to support creation and development of national young academies and to cooperate with them. The number of GYA members is 200. The GYA membership can be granted to scientists younger than 35, the membership term is four years. The membership conditions are high qualification and achievements in R&D, to be supported by recommendations of outstanding scientists from any national organization of an applicant’s country. The Ukrainian practices in creating youth entities in R&D are shown by case of Councils of Young Scientists. It is concluded from the analysis that Ukraine actually needs to create an organization analogous to the young academy, to have talented youth engaged in R&D.